Experimental evaluation of BCG vaccine and proteic extract in bovines, via cytokine expression - Cruz-Fierro, Maura; Jaramillo-Meza, Laura; Espitia Pinzón, Clara Inés; Pérez-González, Rafael; Manzo-Sandoval, Anabelle; Díaz-Otero, Fernando (Spei Domus, 2020)
Introduction: bovine tuberculosis (bTB) continues to be a serious public and animal health issue, specially in developing countries, in which prevalences in bovine dairy systems can reach numbers above 40%. Consequently, its control must be grounded in whole alternatives for its animal source in order to prevent transmission between animals and human beings from a “one health” perspective. Vaccination is considered the most viable option to reduce its incidence; nonetheless, to achieve this purpose successfully is necessary to determine the conditions under which vaccine must be applied, and understand the immunological mechanisms giving resistance against mycobacterium bovis, since its an intracellular bacteria it is desirable that vaccines induce a Th1 type response, characterized by gamma interferon production (IFNγ), which is a tumor necrosis factor alpha (TNF) and interleukin 12 (IL-12), cytokines responsible for macrophage microbicide activation and effect. This study evaluated vaccination effectiveness of BCG vaccine and proteic extract filtered from a m. Bovis (CFPE) culture as immuno agent against bTB, through monitoring of IFNγ production, evaluation of cytokines Th1 expression (IFN-g, IL-2), Th2 (IL-4, IL-10), and the presence of macroscopic lesions towards necrosis after the challenge. Methodology: 24 Holstein-Friesian calves of six months old, negative to different bTB immunodiagnostic tests, were devided in four groups (6 calves/group): not vaccined group, BCB vaccined, vaccinated with CFPE m. Bovis AN5 and vccinated with CFPE, but with previous IFNγ treatment. IFNγ, IL-2, IL-4 and IL-10 cytokine expression was evaluated through RT-PCR and represented as the percentage of relative intensity to corresponding bands with respect to internal positive control (b-actin), using LabWorks 4.0 software. Immune cellular response was evaluated through IFNγ production in cell culture estimated with bovine and avian PPD in different periods. Results: cytokine expression was different between vaccinated and control groups, both in the postvaccinal and postchallenge periods. Expression of IFNγ in vaccinated group with BCG was higher in front of in vitro antigen stimulation with bovine PPD and with DipZ antigen in the evaluated postvaccination period. Immunized groups with CFPE, expression of IL-4 was significant during that period, specially in group treated with IFNγ. After challenge, production and expression of IFNγ increased in all groups; being 200 times higher for the group treated with IFNγ with different antigen. In this group, higher expression of IL-2, IL-4 and IL-10 was also significant, especially IL-10, a known antagonist of cellular immunity. In fact, this vaccinated group presente the highest number of lesions to challenge; being, nonetheless, less severe than the ones in the control group. Conclusions: the vaccinated group with BCG registered the lower number and degree of lesions, correlated with a significant IFNγ expression and production. Previous treatment with IFNγ in the immunized group with CFPE showed an adverse effect in the stablishment of a protective immunity due to a negative modulation from IL-4 and IL-10. According to the results, BCG is a better immune agent in the study, so that its use as an alternative for disease control is promising.
Keywords: bovine; cytokines; gamma interferon; tuberculosis; BCG vaccine